Csánki (Csánky) Benjámin teológus professzor, a Debreceni M. Kir. Tisza István Tudományegyetem 1929/30. tanévi rector magnificusa - Ferencz, Árpád (Gerundium, 2017)
Benjámin Csánki (Csánky), Professor of Theology, the Rector Magnificus of the Hungarian Royal István Tisza University of Debrecen during the Academic Year 1929/30. It was during Csánki’s rectorship that the construction of the Main Building of the University was completed, together with the professors’ residential villas. The structure of the university library was also outlined in the said period. Again, it was during the time referred to that serious negotiations were launched for the purposes of establishing universitylevel education for the agrarian program in Debrecen. The building of the university church and the construction of the modern student dormitories were also undertaken during this time. Besides offering an overview of the events of the rectorial year, the present discussion, by also looking at specific writings by him, evaluates Csánki’s most characteristic theological works.